Experimental behavior of iron-based shape memory alloys under cyclic loading histories. (22nd February 2021) - Rosa, Diego Isidoro Heredia; Hartloper, Alexander; de Castro e Sousa, Albano; Lignos, Dimitrios G.; Motavalli, Masoud; Ghafoori, Elyas
Highlights: The behavior of iron-based shape memory alloys under cyclic straining is investigated. A broad range of uniaxial cyclic strain histories representing earthquake loading is used. Iron-based shape memory alloys (Fe-SMA) exhibit asymmetric stress-strain relation. The cyclic behavior of Fe-SMAs is strain-rate and temperature dependent. The hardening response of Fe-SMAs is appreciably higher than conventional steels. Abstract: The present paper investigates the behavior of iron-based shape memory alloys (Fe-SMAs) subjected to cyclic inelastic straining by means of uniaxial coupon experiments. The tests feature round bar coupons subjected to a broad range of uniaxial cyclic strain histories representative of earthquake loading. The experimental results suggest that the Fe-SMA under investigation exhibits an asymmetric stress-strain relation, with limited superelastic behavior. It was found that the post-yield/phase transformation behavior of the Fe-SMA alloy is both strain-rate and temperature-dependent. Quantitative comparisons with structural steels subjected to nominally identical cyclic strain histories indicate that, although the studied Fe-SMA has a similar energy dissipation per loading excursion with respect to conventional S355J2+N, the Fe-SMA's hardening response is appreciably higher, leading to comparatively larger elastic strain energies being stored.